Opinions on smoking and smoking cessation: a qualitative research - (:unkn) unknown (My University, 2014)
0

OBJECTIVE: The aim of this research was to determine the views of both smokers and non-smokers on smoking and cessation of smoking. MATERIAL AND METHODS: This research was the focus group study performed with 33 subjects participating in the Balcova Heart Project (BHP). RESULTS: The smokers described smoking mostly as a friend whereas non-smokers described smoking as illness and unsoundness and associated with death. The smokers indicated that the causes of cigarette smoking were a way of coping in difficulty and being accepted as friends; however, non-smokers indicated the cause of smoking was “pretension”. All of them reported that the basic factor for cessa- tion of smoking is self-control. Smokers signified that service for cessation of smoking should be free, continuous, and applied by experts. Informational meetings should have explanations of methods of cessation of smoking, affectivity in smoking cessation process, and health differences after cessation smoking. CONCLUSION: Perceptions of smokers and non-smokers on cigarette were different. Services related to cessation of smoking should be free, continuous, and given by experts.
Keywords: Kulak, Burun, Boğaz; Solunum Sistemi